Pengaruh Perbandingan Puree Wortel (Daucus carota L.) Dan Terigu Terhadap Karakteristik Roti Tawar - Yunita, Norma; Sugitha, I Made; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This research was conducted with the to determine the comparative effect of carrot puree and wheat flour on the characteristic of bread and to know of the exact comparison of carrot puree and wheat flour to obtain the best characteristic of bread. The experimental design used was a Randomized Block Design (RBD) with treatment factor ratio of carrot puree and wheat flour that was 0%: 100%, 10%: 90%, 20%: 80%, 30%: 70%, 40%: 60%, and 50 %: 50%. The treatment was repeated 3 times to obtain 18 experimental units. Data were analyzed with the Anova test and if the treatment had an effect on the variables then proceeded with the Duncan test. The results showed that the comparison of carrot puree and wheat flour affected the water content, ash content, swelling power, total carotene, color, aroma, texture, taste, pore uniformity, and overall acceptance. Comparison of 30% carrot puree: 70% wheat flour produced the best characteristics of bread with the criteria water content of 16.13%, ash content of 1.37%, loaf volume of 123.65% and total carotene content of 13.01 mg/100 g. Orange color, slightly carrot aroma, soft texture, pore uniformity (uniform) liked and overall acceptance of bread very liked. Keywoards : bread, wheat flour, carrot puree.